A Fast Track Recovery Program Significantly Reduces Hospital Length of Stay Following Uncomplicated Pancreaticoduodenectomy - Nikfarjam, Mehrdad; Weinberg, Laurence; Low, Nicholas; Fink, Michael A; Muralidharan, Vijayaragavan; Houli, Nezor; Starkey, Graham; Jones, Robert; Christophi, Christopher (JOP. Journal of the Pancreas, 2013)
Context Factors affecting length of hospital stay after uncomplicated pancreaticoduodenectomy have not been reported. We hypothesized that patients undergoing uncomplicated pancreaticoduodenectomy treated by fast track recovery program would have a shorter length of hospital stay compared to those managed by a standard program. Methods Patients without surgical or medical complications following pancreaticoduodenectomy managed by fast track or standard protocols, between 2005 and 2011, were identified and prognostic predictors for length of hospital stay determined. Results Forty-one patients treated by pancreaticoduodenectomy had no medical or surgical complications during this period. Of these patients, 20 underwent fast track recovery program compared to 21 who underwent standard care. Patients in the standard group were more likely to have a feeding jejunostomy tube (P<0.001), pylorus preserving procedure (P=0.001) and a nasogastric tube in place longer than 24 hours postoperatively (P<0.001). The median postoperative length of stay was shorter in the fast track recovery program group (8 days, range: 7-16 days) versus 14 days, range: 8-29 days; P<0.001). There were three readmissions in the fast track recovery program related to abdominal pain and none in the standard group. The overall length of stay, accounting for readmissions, still remained significantly shorter in the fast track recovery program group (median 9 days, range: 7-17 days versus median14 days, range: 8-29 days ; P<0.001). There were no significant differences in discharge destination between groups. On multivariate analysis, the only factor independently associated with postoperative discharge by day 8 was fast track recovery program (OR: 37.1, 95% CI: 4.08-338; P<0.001). Conclusion Fast track recovery program achieved significantly shorter length of stay following uncomplicated pancreaticoduodenectomy. Image: Logo (University of Melbourne, Austin Health. Heidelberg, Victoria, Australia).